2019
DOI: 10.1055/a-0753-2285
|View full text |Cite
|
Sign up to set email alerts
|

Funktionelle Kniestabilität im Handball: Ein unverzichtbares Kriterium für sicheren Sport

Abstract: ZusammenfassungVerschiedene Untersuchungen in den vergangenen Jahren haben gezeigt, dass innerhalb der Ballsportarten Handballspieler einem besonders hohen Verletzungsrisiko ausgesetzt sind. Dabei ist das Kniegelenk die am häufigsten verletzte Körperregion und ein Riss des vorderen Kreuzbandes die häufigste Verletzung am Knie. Um Folgeschädigungen oder erneuten Verletzungen vorzubeugen, ist eine gute situative Kniestabilität entscheidend. Diese kann nicht nur Verletzungen vorbeugen, sondern ist auch ausschlagg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…However, other articles present more open definitions. This is the case of Ruehlemann et al [ 20 ] (2019) and Monaco et al [ 22 ] define injury as damage that causes absence in training or competition. In the case of Asker et al [ 2 ] and Aasheimen et al [ 1 ] we are told that it causes a moderate or severe reduction in training volume, performance or even total capacity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other articles present more open definitions. This is the case of Ruehlemann et al [ 20 ] (2019) and Monaco et al [ 22 ] define injury as damage that causes absence in training or competition. In the case of Asker et al [ 2 ] and Aasheimen et al [ 1 ] we are told that it causes a moderate or severe reduction in training volume, performance or even total capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Along these lines, Oshima et al [ 25 ] reported that those players who sustained ACL injuries had poor static balance compared to players who were not injured, concluding that balance training is effective in preventing non-contact ACL injuries. In the study presented by Ruhlemann et al [ 20 ], they evaluated knee stability functionality with a battery of tests, finding that stability differs depending on the position on the field. The results of this study show that the pivot is the player with the best stability values in the two-legged stability test, while in the single-legged balance, it was the wingers who obtained the lowest results.…”
Section: Discussionmentioning
confidence: 99%
“…Reasonable test and measures therefore involve tasks in jumping 18 , landing 13 , side-cutting 19 20 and balance 21 22 and are summarized as “functional knee stability” 23 . Unfortunately, scientific studies measuring functional knee stability in an objective manner in handball are lacking 24 25 . Moreover, most of the recent studies in handball examined professional players in national teams or elite divisions of the respective country.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, such information can help to identify physical deficits beforehand to prevent knee injuries. So far, no reference data in handball exist [45]. Scientific studies measuring functional knee stability in an objective manner in handball are lacking, especially in non-elite sports.…”
Section: Introductionmentioning
confidence: 99%